Student perceptions of the ‘best’ feedback practices: An evaluation of student-led teaching award nominations at a higher education institution - Lowe, Tom; Shaw, Cassie (Teaching and Learning Inquiry, 2019)
There is great emphasis in contemporary higher education to address the seemingly consistent issue of what students perceive to be good assessment feedback practice. Improving this aspect of the student experience continues to elude higher education institutions, as reflected in the nationally lower than average scores in the United Kingdom’s annual National Student Survey questions on prompt feedback, which makes this a timely area for further investigation and discussion. To investigate student perceptions of feedback, this article examines the qualitative data from three years of student-led teaching awards nominations at the University of Winchester for the category "Best Lecturer for Constructive and Efficient Feedback." From this study, new revelations with regard to the student perception of the “best” lecturers’ feedback practices have come to light, including terminology, language, and emphasis on email turnaround, rather than the actual format of the feedback itself (such as handwritten, audio, e-submission). Key findings include that students focus on the quality of the linguistic elements of feedback rather than the mode of delivery. The study also finds that students are often perceiving feedback in a literal sense, with many staff nominated based on their informal email responses rather than the formal assignment feedback often attributed to this question in the National Student Survey. In order to tease out the repetitive emerging themes for which practices students are perceiving to be “good” feedback, this article outlines the findings of this study, including the methodology and nomination process of the student-led teaching awards at the University of Winchester.